Does increasing women's education reduce their risk of intimate partner violence?: evidence from an education policy reform - Weitzman, Abigail (Criminology, 2018)
Although scholars have employed rigorous causal methods to examine the relationship between education and crime, few of them have taken a causal approach to the study of education and intimate partner violence (IPV) specifically. From a social causation perspective, improving women's education should protect them from violence, yet from a social selection perspective, education could proxy for unobserved factors that explain negative associations between education and IPV. In this study, I adjudicate between the two possibilities using an exogenous source of variation in education—a 1990s compulsory schooling reform in Peru. Specifically, I conduct an instrumented regression discontinuity that implicitly controls for women's unobserved endowments by comparing women who were aged slightly younger (N = 8,195) and slightly older (N = 6,645) than the school‐age cutoff at the time of the reform. Consistent with the social causation perspective, increasing women's schooling reduced both their recent and longer term probabilities of psychological, physical, and sexual IPV, as well as their recent and longer term probabilities of experiencing any IPV and polyvictimization. The results of supplemental mediation analyses provide support for three interrelated causal pathways—improvements in women's personal resources, delayed family formation, and changes in partner selection. These findings confirm the protective effects of women's education and further illuminate the mechanistic processes by which this occurs.